“Fuentes de N,P,k, y micronutrientes en presencia y ausencia de fierro quelatado en el cultivo de sacha inchi (plukenetia volubilis L.).- tarapoto-San Martín” - Paulino Córdova, Jonathan Brian (2015)
The research took place in the Quarantine estate area ceded by the Regional Oirectorate of Agricutture m San Martin-(ORASAM) ·focated in 1he wmict of Tarapoto, province and region of San Martin. lt is geographically located at 06 º 30 '39' 'south latitude and 76 º 22' 53" west longitude atan altitude of 260 msnmm in August 2013 and ended in Mareh 2614 at the tnstitute of Amazorrian Researetr Peruana (ttAP - San Martin). The reseatch is to~ ''SOURCES OF ·tt, P, K and' MtCRONUTRtENT tN THE PRESENCE ANO ABSENCE OF IRON CHELA TED GROWING SACHA INCHI (Plukenetia volubilis L.). - TARAPOTO- SAN MARTIN, PERU" To ·studf 1he biolog.cat assay m pots, we used 1he Ptica'dpa eootfPe from ttre native community of Lamas - "Pucallpa" which were selected from free plantations phytosanitary problems in high yield and soil material used from the 2 May hamlet, dtsbict of San Pabto, Betfavista provitrce, depattment of San Malfut. A completely randomized design factorial arrangement of 2 x 6 with sources (arr.monium nmate, tF.pte superphosphate ar.O- potassram etdortde wittr 100-60 -100) and micronutrients (OLIGOMIX) with three replications and six treatments presence without presence of chelated iron was the type of design applied to this research. The variabtes ewk:tcñ~ ami statisticaHy analJzed were 1nitfat· analysis ot son·, ptant height, and stem diameter, number of leaves, root volume and dry matter (leaf, stem and root). Y4fth- the appfieaf.oo of ehetated Fe ~ of 1he ~ of HPK + Mieron, the largest average plant height, stem diameter, number of leaves, fresh volume of roots, fresh weight of root and leaf fresh weight were obtained with 137.04 cm, 5.53 mm, 35.1teaves,49.72mt, 33.56gand 17.33g~~ The absence of chelated iron in soils with high levels of calcium carbonates in vegetative ~ of sacha 'inchi· crop aHows the presence of iron ch1orosis in its development.